Reducing the Cost of Grid Extension for Rural Electrification - NRECA International, Ltd. (World Bank, Washington, DC, 2014)
This study first reviews the cost of grid extension in a number of countries. It then identifies ways to reduce costs by examining how they are affected by a variety of factors. An electricity supply system may be divided into two discrete components: the grid extension and the low-voltage distribution system. This study will focus on the first of these two components, the cost of grid extension. Three questions asked are: 1) What factors give rise to the costs commonly associated with grid extension for rural electrification? 2) Are high costs intrinsic to grid extension? If not, what has been learned from experiences around the world about technical design options that can reduce the capital cost incurred in line construction as well as the recurring costs incurred in operating the system? 3) How low can these costs typically be?